DETERMINANTS OF TAX AVOIDANCE IN INDONESIA - Hartinah, Siti; Ais, Ghina Ridahatul (Universitas Jember, 2024)
ABSTRACTThe research aims to understand and test that tax avoidance can be influenced by audit committees, political connections, CSR and profitability. The research uses a quantitative research approach and data sources are obtained from annual financial reports. The population was obtained from mining sub-sector companies in Indonesia. Meanwhile, to determine the sample using a purposive sampling technique with samples that met the criteria of 15 companies and were studied over a 5 years period, namely 2017-2021 with a total of 75 samples. Meanwhile, to test the data and analyze it using multiple linear regression with the SPSS version 27 measuring tool. The results of this research state that Tax Avoidance cannot be significantly influenced by the Audit Committee. Meanwhile, Tax Avoidance can be influenced in a significantly positive direction by Political Connections. Profitability and Corporate Social Responsibility have a negative effect on Tax Avoidance.Keywords: Audit Committee; CSR; Political Connections; Profitability; and Tax Avoidance. ABSTRAKPenelitian ini bertujuan untuk memahami dan menguji tax avoidance dapat dipengaruhi oleh komite audit, koneksi politik, CSR dan profitabilitas. Penelitian menggunakan metode dengan penelitian pendekatan kuantitatif dan sumber data diperoleh dari laporan keuangan tahunan. Populasi diperoleh dari perusahaan sub sektor pertambangan di Indonesia. Sementara itu, untuk menentukan sampel menggunakan teknik purposive sampling dengan sampel yang memenuhi kriteria sebanyak 15 perusahaan dan yang diteliti selama periode 5 tahun yaitu 2017-2021 dengan total 75 sampel. Sedangkan, untuk menguji data dan menganalisis menggunakan regresi linier berganda dengan alat pengukur program SPSS versi 27. Hasil dari penelitian ini menyatakan Tax Avoidance tidak dapat dipengaruhi secara signifikan oleh Komite Audit. Sementara itu, Tax dapat dipengaruhi dengan arah positif secara signifikan oleh Koneksi Politik. Untuk Profitabilitas dan Corporate Social Responsibility berpengaruh dengan arah negatif terhadap Tax Avoidance.Kata Kunci: CSR; Komite Audit; Koneksi Politik; Profitabilitas; dan Tax Avoidance.